Analisis Kelemahan Perlindungan Korban Perempuan Victim Blamming dalam Kekerasan Seksual - Mohammad Krisna Wibowo; Sigit Sapto Nugroho; Anik Tri Haryani (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
The implementation of Law Number 12 of 2022 concerning Sexual Violence Crimes (TPKS Law) and the Law on the Protection of Witnesses and Victims in addressing the practice of victim blaming. This study employs a normative legal method with statutory, conceptual and case approaches. The results show that, normatively, the TPKS Law and the Law on the Protection of Witnesses and Victims have provided a victim-oriented framework of protection. However, in practice, there are still obstacles in the form of social stigma, victim blaming practices and limited institutional capacity, which result in low case reporting and suboptimal legal protection for victims of sexual violence in Indonesia.